2000
DOI: 10.1523/jneurosci.20-06-j0004.2000
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Enhances Working Memory by Modulating Discrete Frontal and Parietal Lobe Regions in the Human Brain

Abstract: The indirect catecholamine agonist methylphenidate (Ritalin) is the drug treatment of choice in attention deficit/hyperactivity disorder (AD/HD), one of the most common behavioral disorders of childhood (DSM-IV), although symptoms may persist into adulthood. Methylphenidate can enhance cognitive performance in adults and children diagnosed with AD/HD (Kempton et al., 1999; Riordan et al., 1999) and also in normal human volunteers on tasks sensitive to frontal lobe damage, including aspects of spatial working m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
414
6
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(484 citation statements)
references
References 31 publications
(47 reference statements)
51
414
6
13
Order By: Relevance
“…Other researches studying the effects of methylphenidate on spatial memory performance, however, have shown memory performance improvement in young healthy volunteers (Elliott et al 1997;Mehta et al 2000). Elliott et al (1997) showed that methylphenidate (20 and 40 mg) improved performance on a spatial span task and a search tokens task as compared to placebo, when the methylphenidate session preceded placebo sessions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other researches studying the effects of methylphenidate on spatial memory performance, however, have shown memory performance improvement in young healthy volunteers (Elliott et al 1997;Mehta et al 2000). Elliott et al (1997) showed that methylphenidate (20 and 40 mg) improved performance on a spatial span task and a search tokens task as compared to placebo, when the methylphenidate session preceded placebo sessions.…”
Section: Discussionmentioning
confidence: 98%
“…These facilitating effects of the drug were determined by the familiarity with the task (novelty of the task) and consequently only showed when subjects received methylphenidate on the first session. Mehta et al (2000) showed that the size of effect of methylphenidate (40 mg) on spatial memory correlated negatively with the baseline working memory capacity. This capacity was determined by performance on a span task, before administration of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, we expected that performance would deteriorate under a DA agonist given that (1) DA agonists can worsen psychotic symptoms in patients with schizophrenia (Davidson et al, 1987;Abi-Dargham et al, 1998) and trigger psychotic symptoms in healthy participants (Janowsky and Risch, 1979;Sekine et al, 2001); (2) schizotypy and schizophrenia share cognitive (Gooding et al, 1999;Park, 1999), attentional (Sarkin et al, 1998;Mohr et al, 2003a), behavioral (Barnett and Corballis, 2002;Mohr et al, 2003b), and physiological (Klein et al, 1999;Pizzagalli et al, 2000) similarities; and (3) DA agonists increase stereotyped responding in animals (Randrup and Munkvad, 1974;Staton and Solomon, 1984;Kelley et al, 1988) and healthy populations (Connell, 1958;Ridley et al, 1988). Findings from animal (Arnsten, 1997;Williams and Goldman-Rakic, 1995) and human (Mehta et al, 2000) studies propose that dopaminergic actions follow an inverted Ushape function, with an improvement of cognitive performance from low to medium, but deterioration from medium to high doses. This characteristic inverted U-shape function is thought to explain DA actions on cognition as a function of individuals' overall baseline performance.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic inverted U-shape function is thought to explain DA actions on cognition as a function of individuals' overall baseline performance. Animals (Granon et al, 2000) and humans (Kimberg et al, 1997;Mattay et al, 2000;Mehta et al, 2000) performing low at baseline profited from the substance and those performing high at baseline deteriorated after substance intake. Thus, applied to the present study, individuals performing low in the substance-free state (high MI scorers in Experiment 1 and the placebo group of Experiment (2) performed best in the levodopa group.…”
Section: Discussionmentioning
confidence: 99%
“…In the interpretation of psychopharmacological studies of cognition, the influence of baseline performance on subsequent response to a drug challenge has been discussed by a number of authors (Robbins and Sahakian 1979;Kimberg et al 1997;Mattay et al 2000;Mehta et al 2000). Tasks of working memory and executive function may be both impaired (Kimberg et al 1997) or improved (Kimberg et al 1997;Mehta et al 2000) following dopaminergic agonists, dependent on baseline working memory capacity.…”
Section: Letter To the Editormentioning
confidence: 99%